The weekenders [large type] - Andrews, Mary Kay, 1954- (Wheeler Publishing, 2016)
"Some people stay all summer long on the idyllic island of Belle Isle, North Carolina. Some people come only for the weekends-and it's something they look forward to all week long. When Riley Griggs is waiting for her husband to arrive at the ferry one Friday afternoon, she is instead served with papers informing her that her island home is being foreclosed. To make matters worse, her husband is nowhere to be found. She turns to her island friends for help and support, but each of them has their own secrets and the clock is ticking as the mystery deepens. Riley must find a way to investigate the secrets of Belle Isle and the husband she might not really know" -- Back cover.